Study on the Relationship Between Oolong Tea Brand Packaging Design and Color - Hou, Tian; Park, Jongbin (International Journal of Global Economics and Management, 2024)
The color design in the packaging of Oolong tea brand plays an important role in the sales and business activities of the goods. In the contemporary packaging design of Oolong tea brand, the color design has been placed in a crucial position. This paper mainly starts from the relationship between oolong tea brand packaging design and color, firstly discusses the importance of color in Oolong tea brand packaging design, secondly studies the relationship between Oolong tea brand packaging design and color, and finally discusses the application of color in Fujian Oolong tea brand packaging design.